2018
DOI: 10.1542/peds.2018-3074
|View full text |Cite
|
Sign up to set email alerts
|

Sport-Related Concussion in Children and Adolescents

Abstract: Sport-related concussion is an important topic in nearly all sports and at all levels of sport for children and adolescents. Concussion knowledge and approaches to management have progressed since the American Academy of Pediatrics published its first clinical report on the subject in 2010. Concussion's definition, signs, and symptoms must be understood to diagnose it and rule out more severe intracranial injury. Pediatric health care providers should have a good understanding of diagnostic evaluation and init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
131
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(141 citation statements)
references
References 245 publications
2
131
0
Order By: Relevance
“…Current recommendations suggest that a period of physical and cognitive rest be prescribed following the concussion and the nature and duration of rest be modified as the patient recovers [36][37][38]. With recent emphasis on cognitive rest and academic accommodations [39][40][41], the findings reinforce the need to capture general fatigue, cognitive fatigue and school functioning, among other HRQoL measures.…”
Section: Discussionmentioning
confidence: 94%
“…Current recommendations suggest that a period of physical and cognitive rest be prescribed following the concussion and the nature and duration of rest be modified as the patient recovers [36][37][38]. With recent emphasis on cognitive rest and academic accommodations [39][40][41], the findings reinforce the need to capture general fatigue, cognitive fatigue and school functioning, among other HRQoL measures.…”
Section: Discussionmentioning
confidence: 94%
“…In reference to attitudes towards PE, the most highly rated dimension is agreement with subject management relating to PE [52], in contrast to the usefulness of this subject which demonstrated a trend towards considering PE as of little use [53,54]. On the contrary, numerous studies positively rate the usefulness of engaging in sport and PA on a daily basis [55,56]. This positive evaluation of the usefulness of PE leads to intrinsic motivation for engaging in PA, both inside and outside of the school timetable [57].…”
Section: Discussionmentioning
confidence: 99%
“…Without pathognomonic imaging findings or laboratory tests available, health care professionals who diagnose and treat pediatric patients with concussion rely heavily on self-reported symptom inventories to gauge injury severity and develop management strategies. 3 Although longitudinal research 4 indicated that most youth who sustained concussions did not demonstrate long-term symptoms or neurocognitive impairment, investigators 5 have proposed that children and adolescents are more likely to experience prolonged recovery periods than adults. In the small subset of youth who experienced prolonged symptoms or neurocognitive problems, negative effects on various domains of health-related quality of life have been well described.…”
mentioning
confidence: 99%